Website expenditure and taxation ruling TR 2001/6 (Corporate education channel, 2001)
The development of e-commerce has thrown up a number of new tax and accounting issues, one of which is how to account for website expenditure for both tax and financial statement purposes. This program reviews TR 2001/6, the final ruling on taxation treatment of website expenditure.